Migraţia de întoarcere a românilor din Italia. Studiu de caz în Vulturu, Vrancea - Vlase, Ionela (Calitatea Vieții, 2011)
Romanian migration to Italy witnessed a series of structural changes, in the past two decades. Romanians were first illegal migrants in search for informal jobs, and became legal migrants in 1998 and 2002, when they legalized their status, due to the Italian regularization campaigns. Global economic and political contexts, as well as different individual socioeconomic characteristics featured migrants’ experiences differently. A recent pattern is the return to Romania. Romanians planned their migration as temporary and, therefore, we can expect important rates of return. In the past years, return becomes more visible in some migrant communities. The research aims at shedding light on the determinants of return migration from Italy to their place of origin, Vulturu, situated in Vrancea County. Different levels of economic, cultural, and social capital can issue opposite patterns of reintegration of the returnees, in respect to the transferability of skills learned abroad, quantity and quality of the stock of social capital in migrants’ origin countries, and economic opportunities. Moreover, men and women have worked in different domains in Italy and tend, therefore, to have unequal chances to participate in the labor market of their region of origin